Pembentukan Sikap Toleransi Beragama Siswa Melalui Pembelajaran Pendidikan Agama Islam di SMK Negeri 4 Palangka Raya - Putri Marlia; Ahmadi Ahmadi; Saiful Lutfi (Jayapangus Press, 2025)
In this research, the problem studied is the formation of students' attitude of religious tolerance through the learning of Islamic Religious Education in vocational schools. Religious diversity in vocational schools is a challenge for students in their daily activities, this requires PAI teachers to provide explanations and train students to be tolerant in order to respond wisely to religious diversity. The researcher sought to find the elements that inhibit tolerance, as well as their impact on student behavior. Problems that contribute to students' limited understanding, the impact of social media, inconsistent teaching examples, and inadequate time. It is important for every student to have an attitude of tolerance so that there are no divisions, conflicts that trigger commotions, condescending attitudes between others, avoiding bullying because this attitude is very bad in its impact on mental health and lowering someone's confidence. Through the subject of Islamic Religious Education (PAI) at SMK Negeri 4 Palangka Raya, it is hoped that students will have a good attitude of religious tolerance where they help each other, blend in with each other, cooperate, and respect the beliefs of others who are of different religions, and can live in harmony and side by side. The methodology used is a descriptive qualitative approach using a case study research design. Data for this study were collected through observation, interviews, and documentation. The research participants were three Islamic Religious Education (PAI) teachers and six students, in addition to the documentation study. The data obtained is then analyzed through the process of data reduction, presentation, and verification. The process of forming tolerance is carried out through targeted PAI learning planning, the application of discussion methods, and the example of teachers in instilling mutual respect between religious communities. After that, this study details the factors that influence the process, including the influence of educators, inclusive education policies, interfaith initiatives, and family and community support. As a result, students show increased appreciation for differences, avoid discrimination, and be more sensitive to diversity. This research shows that Islamic Religious Education (PAI) makes a significant contribution to increasing religious tolerance, depending on cooperation between teachers, schools, families, and communities.